Nanocellulose and its dispersion and its manufacturing method

By controlling the fiber length and width distribution parameters of nanocellulose, the viscosity stability of nanocellulose slurries is improved, addressing the challenges of consistency and quality in existing technologies.

JP7649459B2Active Publication Date: 2025-03-21TOAGOSEI CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022539519
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-28
Filing Date
2021-07-28
Publication Date
2025-03-21
Estimated Expiration
2041-07-28

AI Technical Summary

Technical Problem

Existing nanocellulose technologies face challenges with viscosity stability in slurries, particularly due to variations in fiber length and width distributions, which affect the quality and consistency of products.

Method used

By controlling the standard deviation, kurtosis, skewness, or range of the fiber length or width distributions of nanocellulose within specific ranges, the viscosity stability of nanocellulose slurries is significantly improved.

Benefits of technology

The controlled fiber distribution parameters enhance the viscosity stability of nanocellulose slurries, making them more suitable for applications as thickeners, dispersants, and binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649459000001
    Figure 0007649459000001
  • Figure 0007649459000002
    Figure 0007649459000002
  • Figure 0007649459000003
    Figure 0007649459000003
Patent Text Reader

Abstract

The present invention provides nanocellulose that produces nanocellulose-containing slurry having stable viscosity, the nanocellulose having an average fiber length of 100-500 nm, an average fiber width of 2.0-5.0 nm, and satisfying at least one of the following conditions. Condition A: the standard deviation of the fiber length is 600 nm or less. Condition B: the kurtosis of the fiber length is 11 or greater. Condition C: the skewness of the fiber length is 3.0 or greater. Condition D: the range of the fiber length is 4000 nm or less. Condition E: the standard deviation of the fiber width is 1.5 nm or less. Condition F: the kurtosis of the fiber width is 0.3 or greater. Condition G: the skewness of the fiber width is 0.5 or greater. Condition H: the range of the fiber width is 6.8 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nanocellulose and a dispersion thereof, and a method for producing the same. More specifically, the present invention relates to nanocellulose having an average fiber length and an average fiber width in a specific range, and having a fiber length distribution or a fiber width distribution in a specific range, a nanocellulose dispersion containing the same, and a method for producing nanocellulose. [Background technology]

[0002] Nanocellulose, such as cellulose nanofiber (hereinafter also referred to as "CNF"), is produced by mechanically defibrating cellulose, oxidized cellulose, etc. in water, and is obtained as a viscous aqueous dispersion of nanocellulose. Taking advantage of its viscosity, nanocellulose is being considered for use as a thickener, dispersant, binder, etc., but it is known that the viscosity of nanocellulose aqueous dispersions is related to the fiber shape of nanocellulose, such as fiber length and fiber width. In addition, when nanocellulose and inorganic particles are mixed to prepare a slurry for the above-mentioned applications, if the viscosity stability of the slurry is poor, there is a risk of changes in the quality of the product.

[0003] For example, JP 2018-162549 A (Patent Document 1) describes acid (H)-type carboxylated CNF that has high viscosity in the low shear region and extremely short fiber length, with the average fiber length and average fiber width of the CNF specified, and the viscosity of the CNF aqueous dispersion specified.

[0004] Furthermore, Japanese Patent No. 5655432 (Patent Document 2) describes a method for obtaining fine fibrous cellulose having a fiber width of 4 to 100 nm and a fiber length of 1 to 600 μm, which accounts for 30% or more of the total fibers, by mechanically treating chemical pulp to shorten the fibers, followed by treating it with a cellulase-based enzyme, and then performing a fine treatment such as a high-speed rotary defibration treatment, a high-pressure homogenizer treatment, or an ultrasonic treatment. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-162549 A [Patent Document 2] Patent No. 5655432 Summary of the Invention [Problem to be solved by the invention]

[0006] However, Patent Document 1 is a technology related to acid-type carboxylated CNF that has high viscosity in the low shear region, and describes CNF with an average fiber length of 50 to 500 nm, with 50% or more having a fiber length of 300 nm or less and less than 20% having a fiber length of 600 nm or more, but there is a problem with the viscosity stability of a slurry containing this CNF. Furthermore, Patent Document 2 describes only CNFs with fiber lengths in the micrometer range, and does not describe technology related to fine cellulose, which has a fiber length distribution in the nanometer range.

[0007] In view of the above circumstances, the present invention aims to provide nanocellulose having excellent viscosity stability when used in a slurry containing nanocellulose. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors discovered that the viscosity stability of a slurry containing nanocellulose can be excellent by setting the standard deviation, kurtosis, skewness, or range as an index showing the fiber length distribution or fiber width distribution of nanocellulose to a specific range, and thus completed the present invention.

[0009] That is, the first invention of the present invention is nanocellulose having an average fiber length of 100 nm or more and 500 nm or less and an average fiber width of 2.0 nm or more and 5.0 nm or less, and satisfying at least one of the following conditions A to H. Condition A: The standard deviation of fiber length is 600 nm or less. Condition B: The kurtosis of the fiber length is 11 or more. Condition C: The fiber length skewness is 3.0 or more. Condition D: Fiber length range is 4000 nm or less Condition E: The standard deviation of the fiber width is 1.5 nm or less. Condition F: The kurtosis of the fiber width is 0.3 or more. Condition G: The fiber width skewness is 0.5 or more. Condition H: Fiber width range is 6.8 nm or less

[0010] The second invention of the present invention is the nanocellulose according to the first invention, in which the standard deviation of the fiber length is 10 nm or more and 500 nm or less.

[0011] The third invention of the present invention is the nanocellulose according to the first or second invention, in which the kurtosis of fiber length is 12 or more and 30 or less.

[0012] A fourth aspect of the present invention is the nanocellulose according to any one of the first to third aspects of the present invention, wherein the fiber length skewness is 3.0 or more and 6.0 or less.

[0013] A fifth aspect of the present invention is the nanocellulose according to any one of the first to fourth aspects of the present invention, wherein the fiber length is in the range of 450 nm or more and 4000 nm or less.

[0014] A sixth aspect of the present invention is the nanocellulose according to any one of the first to fifth aspects, in which the standard deviation of the fiber width is 0.5 nm or more and 1.5 nm or less.

[0015] A seventh aspect of the present invention is the nanocellulose according to any one of the first to sixth aspects, wherein the kurtosis of the fiber width is 0.3 or more and 2.5 or less.

[0016] An eighth aspect of the present invention is the nanocellulose according to any one of the first to seventh aspects of the present invention, wherein the skewness of the fiber width is 0.5 or more and 1.5 or less.

[0017] A ninth aspect of the present invention is the nanocellulose according to any one of the first to eighth aspects of the present invention, wherein the fiber width is in the range of 3.0 nm or more and 6.8 nm or less.

[0018] A tenth aspect of the present invention is the nanocellulose according to any one of the first to ninth aspects of the present invention, which contains carboxylated nanocellulose.

[0019] An eleventh aspect of the present invention is the nanocellulose according to any one of the first to tenth aspects of the present invention, which is substantially free of N-oxyl compounds.

[0020] The twelfth aspect of the present invention is nanocellulose according to any one of the first to eleventh aspects of the present invention, which is produced by defibrating oxidized cellulose obtained by oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof.

[0021] The thirteenth aspect of the present invention is a nanocellulose dispersion in which the nanocellulose according to any one of the first to twelfth aspects is dispersed in a dispersion medium.

[0022] The fourteenth aspect of the present invention is a method for producing nanocellulose according to any one of the first to twelfth aspects of the present invention, which comprises a step of oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof to obtain oxidized cellulose, and then subjecting the oxidized cellulose to a defibration treatment. Effect of the Invention

[0023] According to the present invention, the viscosity stability of a slurry containing nanocellulose can be improved by setting the standard deviation, kurtosis, skewness, or range of the fiber length of nanocellulose, or the standard deviation, kurtosis, skewness, or range of the fiber width of nanocellulose, within a specific range. Because slurries containing nanocellulose have excellent viscosity stability, the nanocellulose of the present invention is useful, for example, as a thickener, dispersant, binder, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] When a cellulose-based raw material is treated in the presence of 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (hereinafter also referred to as "TEMPO"), sodium bromide, and sodium hypochlorite, an inexpensive oxidizing agent, carboxy groups can be efficiently introduced onto the surface of the cellulose. By defibrating the oxidized cellulose with carboxy groups introduced into it using a mixer or the like, fine nanocellulose with fiber lengths in the nanometer range can be produced. In addition, by treating a cellulose-based raw material with hypochlorous acid or its salt in the absence of TEMPO, oxidized cellulose can be obtained, and by defibrating this, fine nanocellulose can be obtained.

[0025] In addition, since the use of TEMPO may result in harmful N-oxyl compounds remaining in the nanocellulose, nanocellulose that is substantially free of N-oxyl compounds and is obtained by a production method that does not use TEMPO is preferred. In this specification, "substantially free of N-oxyl compounds" means that the residual nitrogen components derived from N-oxyl compounds contained in nanocellulose are 2.0 ppm or less as an increase from the raw pulp. The residual nitrogen components derived from N-oxyl compounds in nanocellulose in this specification are preferably 1.0 ppm or less as an increase from the raw pulp. In addition, when the content of N-oxyl compounds is preferably 2.0 ppm by mass or less, more preferably 1.0 ppm by mass or less as an increase from the cellulose-based raw material, it also means that "substantially free of N-oxyl compounds". By being substantially free of N-oxyl compounds, it is possible to suppress the N-oxyl compounds, which are of concern for their impact on the environment and human body, from remaining in the nanocellulose. The content of N-oxyl compounds can be measured by known means. Known means include a method using a total nitrogen trace analyzer. Specifically, the nitrogen component derived from the N-oxyl compounds in the nanocellulose can be measured as the amount of nitrogen using a total nitrogen trace analyzer (for example, Mitsubishi Chemical Analytech Co., Ltd., device name: TN-2100H, etc.).

[0026] When cellulose is oxidized, carboxyl groups are generated in at least some of the structural units that make up the cellulose molecular chain. The electrostatic repulsion and osmotic pressure effect generated by the carboxyl groups make it possible to defibrate with relatively weak energy, which contributes to reducing production costs. Nanocellulose obtained by this oxidation method is called carboxylated nanocellulose. And since the carboxyl groups improve the dispersibility in water, etc., the viscosity stability of the slurry containing nanocellulose is also improved, so it is preferable that the nanocellulose of the present invention contains carboxylated nanocellulose.

[0027] The nanocellulose of the present invention is an aggregate of nanocellulose fibers. When the nanocellulose of the present invention contains carboxylated nanocellulose, it is sufficient that it contains at least one carboxylated nanocellulose fiber, and it is preferable that the carboxylated nanocellulose is the main component. Here, the fact that the carboxylated nanocellulose fiber is the main component means that the proportion of carboxylated nanocellulose in the total amount of nanocellulose exceeds 50% by mass, preferably exceeds 70% by mass, and more preferably exceeds 80% by mass. The upper limit of the above proportion is 100% by mass, but may be 98% by mass or 95% by mass.

[0028] The nanocellulose of the present invention has an average fiber length of 100 nm or more and 500 nm or less, and an average fiber width of 2.0 nm or more and 5.0 nm or less. The average fiber length is preferably in the range of 100 nm to 450 nm, more preferably in the range of 100 nm to 400 nm. If the average fiber length exceeds 500 nm, the slurry will thicken significantly and handling will become difficult. Also, if the average fiber length is less than 100 nm, it will be difficult to express the viscosity that is a characteristic of nanocellulose.

[0029] The average fiber width is preferably in the range of 2.0 nm to 4.5 nm, more preferably in the range of 2.5 nm to 4.0 nm. If the average fiber width is smaller than 2.0 nm, it is difficult to achieve the strength improvement when nanocellulose is added to a resin. Also, if the average fiber width is larger than 5.0 nm, it is difficult to achieve the strength improvement due to stress concentration.

[0030] The average fiber length and the average fiber width are values ​​calculated by mixing nanocellulose and water so that the concentration of nanocellulose is approximately 1 to 10 ppm, naturally drying the sufficiently diluted nanocellulose aqueous dispersion on a mica substrate, observing the shape of the nanocellulose using a scanning probe microscope, randomly selecting any number of fibers from the obtained image, setting the cross-sectional height of the shape image = fiber width, and setting the perimeter ÷ 2 = fiber length. Image processing software can be used to calculate such average fiber width and average fiber length. At this time, the image processing conditions are arbitrary, but even for the same image, the calculated values ​​may differ depending on the image processing conditions. The range of the difference in value due to the image processing conditions is preferably within ±100 nm for the average fiber length. The range of the difference in value due to the conditions is preferably within ±10 nm for the average fiber width. A more detailed measurement method follows the method described in the examples below.

[0031] With respect to the nanocellulose of the present invention, the standard deviation of the fiber length is preferably 600 nm or less, more preferably 500 nm or less, and even more preferably in the range of 10 nm or more and 500 nm or less. If the standard deviation of the fiber length exceeds 600 nm, the slurry using the nanocellulose is likely to have uneven nanocellulose concentration, and the state of the slurry, especially the viscosity stability, will decrease. Therefore, the smaller the standard deviation, the better. However, if the standard deviation is to be less than 10 nm, the number of times of defibration must be significantly increased, which is not economically preferable.

[0032] For the nanocellulose of the present invention, the kurtosis of the fiber length is preferably 11 or more, more preferably 12 or more, and even more preferably in the range of 12 to 30. Kurtosis is a value that indicates the concentration of fiber length distribution, and a slurry using nanocellulose with a small kurtosis of less than 11 is prone to have uneven areas of nanocellulose concentration, which reduces the state of the slurry, especially its viscosity stability. Therefore, the higher the kurtosis, the better, but to achieve a kurtosis of more than 30, it is necessary to significantly reduce the number of defibrations, which is not preferable as it results in insufficient conversion to nanocellulose.

[0033] With respect to the nanocellulose of the present invention, the skewness (shape of distribution) of fiber length is preferably 3.0 or more, more preferably in the range of 3.0 to 6.0, and even more preferably in the range of 3.0 to 4.0. When the skewness of fiber length is within a certain range, the slurry using nanocellulose has high slurry state, especially viscosity stability, although the mechanism is unclear. If the fiber length skewness is less than 3.0, the viscosity stability decreases, and if the fiber length skewness exceeds 6.0, the number of defibrations must be significantly reduced, which is undesirable because nanocellulose formation will be insufficient. It should be noted that a higher skewness of the fiber length indicates that the fiber length distribution is biased toward the narrower width side.

[0034] Furthermore, with regard to the nanocellulose of the present invention, the range of fiber length (difference between the maximum and minimum values) is preferably 4000 nm or less, more preferably 450 nm or more and 4000 nm or less, even more preferably 500 nm or more and 4000 nm or less, even more preferably 550 nm or more and 4000 nm or less, and even more preferably 700 nm or more and 4000 nm or less. Slurries using nanocellulose with a fiber length range of more than 4000 nm tend to have uneven nanocellulose concentration, which reduces the state of the slurry, especially the viscosity stability. Therefore, the smaller the fiber length range, the better. However, in order to set the lower limit of the fiber length range to less than 500 nm, the number of times of defibration must be significantly increased, which is not economically preferable.

[0035] For the nanocellulose of the present invention, the standard deviation of the fiber width is 1.5 nm or less, preferably in the range of 0.5 nm to 1.5 nm, more preferably in the range of 1.0 nm to 1.5 nm. If the standard deviation of the fiber width exceeds 1.5 nm, the nanocellulose-containing slurry is likely to have uneven nanocellulose concentration in the slurry, and the state of the slurry, especially the viscosity stability, tends to deteriorate. Therefore, the smaller the standard deviation, the better. However, in order to make the standard deviation less than 1.0 nm, it is necessary to significantly increase the number of times of defibration, which is not economically preferable.

[0036] For the nanocellulose of the present invention, the kurtosis of the fiber width is preferably 0.3 or more, more preferably 0.3 to 2.5, and even more preferably 0.7 to 2.5. The lower limit of the kurtosis of the fiber width is more preferably 0.35 or more, even more preferably 0.4 or more, even more preferably 0.5 or more, and even more preferably 0.6 or more. Slurry using nanocellulose with small fiber width kurtosis is prone to have uneven nanocellulose concentration, and the state of the slurry, especially the viscosity stability, tends to deteriorate. Therefore, the larger the kurtosis, the better. However, if the fiber width kurtosis is to exceed 2.5, it is necessary to significantly reduce the number of defibrations, which is not preferable because the nanocellulose conversion will be insufficient.

[0037] For the nanocellulose of the present invention, the skewness (shape of distribution) of the fiber width is preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, and even more preferably 0.8 or more. The range of the skewness of the fiber width is preferably 0.5 to 1.5, more preferably 0.6 to 1.5, even more preferably 0.7 to 1.5, even more preferably 0.8 to 1.5, and even more preferably 0.85 to 1.5. When the fiber width skewness is 0.5 or more, the slurry using nanocellulose has high slurry state, especially viscosity stability, although the mechanism is unclear. If the fiber width skewness is less than 0.5, the viscosity stability decreases, and if the fiber width skewness exceeds 1.5, the number of defibrations must be significantly reduced, which is undesirable because nanocellulose formation will be insufficient. It should be noted that a higher skewness of the fiber width indicates that the fiber width distribution is biased toward the smaller width side.

[0038] Furthermore, for the nanocellulose of the present invention, the range of fiber width (difference between maximum and minimum values) is preferably 6.8 nm or less, more preferably 3.0 nm to 6.8 nm, even more preferably 4.0 nm to 6.8 nm, even more preferably 5.0 nm to 6.8 nm, and even more preferably 5.2 nm to 6.7 nm. Slurry using nanocellulose with a large fiber width range is prone to have uneven nanocellulose concentration, and the state of the slurry, especially the viscosity stability, tends to deteriorate. Therefore, the smaller the fiber width range, the better. However, in order to set the lower limit of the fiber width range to less than 3.0 nm, it is necessary to significantly increase the number of defibrations, which is not economically preferable.

[0039] The average fiber length, average fiber width, standard deviation of fiber length, kurtosis, skewness, and range, and standard deviation of fiber width, kurtosis, skewness, and range in the nanocellulose of the present invention can be controlled within a predetermined range by, for example, selecting the type of cellulose-based raw material, controlling the degree of carboxylation of nanocellulose, specifically, controlling the time of the oxidation reaction; adjusting the stirring of the oxidation reaction; controlling the method of defibration treatment; adjusting the aperture of the filter used in solid-liquid separation of oxidized cellulose after the oxidation reaction; etc. The control methods for the average fiber length, average fiber width, standard deviation of fiber length, kurtosis, skewness, and range, and standard deviation of fiber width, kurtosis, skewness, and range in the nanocellulose of the present invention are not limited to these, and two or more of these methods may be combined. In the method for adjusting the mesh size of the filter, by increasing the mesh size, fine fibers are removed, and the average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of the fiber length, and the standard deviation, kurtosis, skewness, and range of the fiber width can be easily controlled within the specified range.

[0040] In the present invention, the standard deviation of fiber length and the standard deviation of fiber width each indicate how widely the statistically targeted values ​​are distributed from their averages. The standard deviation can be calculated from the following formula (1), where n is the number of data and x is each data.

number

[0041]

number

[0042] With respect to the kurtosis of fiber length and the kurtosis of fiber width, compared to a normal distribution, if the kurtosis is large, the distribution will have a sharper peak and longer, thicker tails, and if the kurtosis is small, the distribution will have a rounder peak and shorter, thinner tails. The kurtosis of the fiber length and the kurtosis of the fiber width can be calculated from the following formula (2), where the number of data is n, each data is xi, and the standard deviation is s.

number

[0043]

number

[0044] Fiber length skewness and fiber width skewness, respectively, measure the degree of asymmetry on either side of the distribution around the mean, with positive skewness indicating a distribution with asymmetric tails extending toward more positive values ​​and negative skewness indicating a distribution with asymmetric tails extending toward more negative values. The skewness of fiber length and the skewness of fiber width can be calculated from the following formula (3), where the number of data is n, each data is xi, and the standard deviation is s.

number

[0045]

number

[0046] The average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of the fiber length, and standard deviation, kurtosis, skewness, and range of the fiber width in the nanocellulose of the present invention may be calculated using a commercially available spreadsheet software. For example, the STDEV function of Microsoft Excel can be used to calculate the standard deviation, the KURT function can be used to calculate the kurtosis, and the SKEW function can be used to calculate the skewness.

[0047] If the average fiber length is relatively short, the fiber length distribution or fiber width distribution is narrow (small standard deviation, small range), and / or the fiber length distribution or fiber width distribution is peaked (high kurtosis), and / or the fiber length distribution or fiber width distribution is biased toward the narrow side (high skewness), it is thought that uneven areas of nanocellulose concentration in the slurry are less likely to occur, and the slurry state, especially the viscosity, will be more stable. Similarly, if the fiber width or fiber width distribution is narrow (small standard deviation, small range) and / or the distribution is peaked (high kurtosis) and / or the fiber width distribution or fiber width distribution is biased toward the narrow side (high skewness), it is believed that uneven areas of nanocellulose concentration in the slurry are less likely to occur, and the slurry state, particularly the viscosity, will be more stable.

[0048] Hereinafter, the nanocellulose of the present invention will be described by way of examples of production methods. Note that the nanocellulose of the present invention is not limited to these production methods. The nanocellulose of the present invention can be produced, for example, by reacting a cellulosic raw material with sodium hypochlorite as an oxidizing agent to produce oxidized cellulose, and then defibrating the oxidized cellulose. Since "nanocellulose" is a fibrous cellulose made by finely grinding oxidized fibrous cellulose, it is also called "fine cellulose fiber" or "CNF." Nanocellulose is also a general term for cellulose that has been made into nanoparticles, and includes cellulose nanofibers and cellulose nanocrystals.

[0049] The cellulosic raw material in the present invention is not particularly limited as long as it is a material mainly composed of cellulose, and examples thereof include pulp, natural cellulose, regenerated cellulose, and fine cellulose obtained by depolymerizing a cellulose raw material through mechanical treatment. In addition, as the cellulosic raw material, commercially available products such as crystalline cellulose made from pulp can be used as they are. The cellulosic raw material may be subjected to a chemical treatment such as an alkali treatment to facilitate the penetration of the oxidizing agent used in the method described below.

[0050] <Process for producing oxidized cellulose> The concentration of the cellulose-based raw material during the reaction is not particularly limited, but is preferably 10 mass % or less, and generally, the reaction is carried out in a state where the cellulose raw material is added to a liquid containing an oxidizing agent. In addition, the effective chlorine concentration of sodium hypochlorite in the reaction system is not particularly limited, but is preferably 6% by mass or more and 43% by mass or less, more preferably 7% by mass or more and 43% by mass or less, even more preferably 10% by mass or more and 43% by mass or less, and even more preferably 14% by mass or more and 43% by mass or less.The higher the effective chlorine concentration in the reaction system, the more smoothly the reaction proceeds.On the other hand, sodium hypochlorite with an effective chlorine concentration of more than 43% by mass is easily unstable.

[0051] The available chlorine concentration in hypochlorous acid or its salts, such as sodium hypochlorite, is a well-known concept and is defined as follows: Hypochlorous acid is a weak acid that exists only as an aqueous solution, and hypochlorites are compounds in which the hydrogen of hypochlorous acid has been replaced by another cation. For example, sodium hypochlorite, a hypochlorite salt, only exists in solution, so the amount of available chlorine in the solution is measured, not the concentration of sodium hypochlorite. The available chlorine in sodium hypochlorite is the oxidizing power of the divalent oxygen atom generated by the decomposition of sodium hypochlorite, which is equivalent to two atomic units of monovalent chlorine, so the combined chlorine atoms in sodium hypochlorite (NaClO) have the same oxidizing power as two uncombined chlorine (Cl2) atoms, and available chlorine = 2 x (chlorine in NaClO). To measure the specific available chlorine concentration, a sample is weighed out, water, potassium iodide, and acetic acid are added, and the sample is allowed to stand. The liberated iodine is then titrated with a sodium thiosulfate solution using an aqueous starch solution as an indicator.

[0052] Methods for adjusting the effective chlorine concentration of an aqueous sodium hypochlorite solution include concentrating an aqueous sodium hypochlorite solution with a low effective chlorine concentration, and adjusting the effective chlorine concentration by using sodium hypochlorite pentahydrate crystals, which have an effective chlorine concentration of approximately 43% by mass, as is or by diluting them with water. The method of adjusting the effective chlorine concentration to the range of 6% by mass or more and 43% by mass or less, which is a preferred range, includes the above-mentioned methods. Among these, it is preferable to use sodium hypochlorite pentahydrate as an oxidizing agent to adjust the effective chlorine concentration, since it has little self-decomposition, that is, the effective chlorine concentration is less decreased, and adjustment is easy.

[0053] The amount of the aqueous sodium hypochlorite solution used as the oxidizing agent can be selected within a range that accelerates the oxidation reaction. The method for mixing the cellulosic raw material and the aqueous sodium hypochlorite solution is not particularly limited, but from the viewpoint of ease of operation, it is preferable to add the cellulosic raw material to the aqueous sodium hypochlorite solution and mix them.

[0054] The reaction temperature in the oxidation reaction is preferably 15° C. to 100° C., more preferably 20° C. to 90° C. In order to efficiently proceed with the oxidation reaction, the pH of the reaction system is preferably maintained at 5 to 14, more preferably 7 to 14. To adjust the pH, an alkali agent such as sodium hydroxide or an acid such as hydrochloric acid can be added. The time for the oxidation reaction can be set according to the degree of progress of the oxidation, but it is preferable to carry out the reaction for, for example, about 15 minutes to 50 hours. From the viewpoint of adjusting the average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of fiber length, and standard deviation, kurtosis, skewness, and range of fiber width, etc., within the ranges of the present invention, the oxidation reaction time is preferably 20 minutes or more, more preferably more than 20 minutes, and even more preferably 25 minutes or more.

[0055] In the oxidation reaction, the primary hydroxyl groups of the cellulose contained in the cellulosic raw material are oxidized to carboxyl groups to generate oxidized cellulose. The oxidized cellulose in the present invention can be said to be oxidized cellulose, which is an oxide of the cellulosic raw material. In addition, when the cellulosic raw material is oxidized with hypochlorous acid or its salt to obtain oxidized cellulose, the oxidized cellulose can be said to be oxidized cellulose, which is an oxide of the cellulosic raw material by hypochlorous acid or its salt. The amount of carboxyl groups in the oxidized cellulose is not particularly limited, but when the oxidized cellulose is defibrated and nano-sized in the next step to produce nanocellulose, the amount of carboxyl groups per 1 g of oxidized cellulose is preferably 0.2 mmol / g or more and 3.0 mmol / g or less, more preferably 0.35 mmol / g or more and 3.0 mmol / g or less, even more preferably 0.4 mmol / g or more and 3.0 mmol / g or less, even more preferably 0.5 mmol / g or more and 3.0 mmol / g or less, and even more preferably 0.55 mmol / g or more and 2.0 mmol / g or less. The oxidation reaction may be carried out in two or more stages.

[0056] In order to improve the viscosity stability of the nanocellulose-containing slurry, the amount of carboxyl groups in the nanocellulose is preferably as high as possible, and is preferably 0.4 mmol / g or more. Because the cost of the oxidation reaction increases, the amount is preferably 0.8 mmol / g or less. The amount of carboxy groups in oxidized cellulose or nanocellulose can be measured by the following method.

[0057] Pure water is added to a 0.5% by mass slurry of oxidized cellulose or nanocellulose to make 60 ml, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5. After that, a 0.05 N aqueous sodium hydroxide solution is added dropwise and the electrical conductivity is measured until the pH reaches 11. The amount of sodium hydroxide consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, is calculated using the following formula. Amount of carboxyl groups (mmol / g oxidized cellulose or nanocellulose) = a (ml) × 0.05 / mass of oxidized cellulose or nanocellulose (g)

[0058] In addition, although the cellulosic raw material may contain protein, the protein contained therein can be removed by filtering and washing with water after the oxidation reaction is completed. Known methods can be used for filtering and washing with water. Furthermore, by comparing the electrical conductivity of the washing water and the washing wastewater, it is possible to determine whether the washing has reached its end point.

[0059] Prior to the above-mentioned isolation treatment such as filtration, in order to improve the filterability and yield of the isolation treatment, an acid is added to the solution containing oxidized cellulose or nanocellulose, for example to adjust the pH to 4.0 or less, and at least a portion of the carboxyl groups produced by oxidation are converted into a salt form (-COO - X + :X + indicates positive ions such as sodium and lithium) to proton type (-COO - H + ) can be used. In the infrared absorption spectrum, the proton type has an absorption peak at 1720 cm -1 Nearby, the salt type is 1600cm -1 They can be distinguished from each other by the presence of peaks in their vicinity.

[0060] When the pH of a solution containing oxidized cellulose or nanocellulose is adjusted to 4.0 or less for the isolation treatment, in order to improve the handling properties for subsequent use, for example, a base is added to adjust the pH to 6.0 or more, and at least a portion of the carboxyl groups are converted to a salt form (-COO - X + :X + indicates a cation such as sodium or lithium). Furthermore, a solution containing oxidized cellulose or nanocellulose may be made into a composition containing oxidized cellulose or nanocellulose by, for example, replacing the solvent. In the composition containing oxidized cellulose or nanocellulose, for example, the pH is made alkaline at 10 or higher, and at least a portion of the carboxyl groups are converted into a salt form (-COO - X + :X +indicates a cation such as sodium, lithium, etc.

[0061] The method for producing oxidized cellulose or nanocellulose may further include a step of mixing the obtained oxidized cellulose or nanocellulose with a compound having a modifying group in order to control the physical properties of the oxidized cellulose. The compound having a modifying group is not particularly limited as long as it has a modifying group capable of forming an ionic bond or a covalent bond with a carboxyl group or a hydroxyl group of the oxidized cellulose or nanocellulose. Examples of compounds having a modifying group capable of forming an ionic bond include primary amines, secondary amines, tertiary amines, quaternary ammonium compounds, and phosphonium compounds. Examples of compounds having a modifying group capable of forming a covalent bond include alcohols, isocyanate compounds, and epoxy compounds. As described above, oxidized cellulose or nanocellulose includes salt forms, proton forms, and forms modified with modifying groups.

[0062] From the viewpoint of adjusting the average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of fiber length, standard deviation, kurtosis, skewness, and range of fiber width, etc., within the ranges of the present invention, it is preferable to use a propeller-type stirring blade or the like that can uniformly mix the reaction system during stirring. The rotation speed of the propeller-type stirring blade is preferably in the range of 50 rpm to 500 rpm, and more preferably in the range of 80 rpm to 200 rpm.

[0063] <The process of defibrating oxidized cellulose to produce nanocellulose> The oxidized cellulose obtained above can be defibrated and nano-sized to produce nanocellulose. The nanocellulose of the present invention includes nano-sized cellulose such as cellulose nanocrystals. In the method of defibrating the oxidized cellulose, the defibration time can be shortened by weak stirring in a solvent using a stirrer or mechanical defibration, but if the mechanical defibration is too strong, the nanocellulose may break or be cut.

[0064] The method of mechanical defibration is not particularly limited, and can be appropriately selected depending on the purpose, for example, after thoroughly washing the oxidized cellulose with a solvent, and examples of such methods include known mixing and stirring devices such as a screw mixer, a paddle mixer, a dispersion mixer, a turbine mixer, a homomixer under high speed rotation, a high pressure homogenizer, an ultra-high pressure homogenizer, a double cylindrical homogenizer, an ultrasonic homogenizer, a water flow opposing collision type disperser, a beater, a disk type refiner, a conical type refiner, a double disk type refiner, a grinder, and a single-shaft or multi-shaft kneader. By treating the oxidized cellulose in a solvent using one or a combination of two or more of these, the oxidized cellulose can be nanosized to produce nanocellulose. From the viewpoint of adjusting the average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of the fiber length, and standard deviation, kurtosis, skewness, and range of the fiber width, within the ranges of the present invention, it is preferable to use an ultra-high pressure homogenizer. When defibration is performed using an ultra-high pressure homogenizer, the pressure during defibration is preferably 100 MPa or more, more preferably 120 MPa or more, and even more preferably 150 MPa or more. The number of times of defibration is not particularly limited, but from the viewpoint of sufficiently progressing defibration, it is preferably 2 times or more, and more preferably 3 times or more. Furthermore, by adjusting defibration conditions such as the number of defibration treatments during mechanical defibration and the concentration of oxidized cellulose in the oxidized cellulose dispersion, the average fiber length, average fiber width, standard deviation, kurtosis, skewness, and range of fiber length, standard deviation, kurtosis, skewness, and range of fiber width, etc. can be brought within the ranges of the present invention.

[0065] The solvent used in the defibration process is not particularly limited and can be selected appropriately depending on the purpose. Examples of the solvent include water, alcohols, ethers, ketones, carbonates, acetonitrile, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc., and these may be used alone or in combination of two or more types.

[0066] Examples of the alcohols include methanol, ethanol, isopropanol, isobutanol, sec-butyl alcohol, tert-butyl alcohol, methyl cellosolve, ethylene glycol, and glycerin. Examples of the ethers include ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran. The ketones include acetone and methyl ethyl ketone. Examples of the carbonate esters include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, diphenyl carbonate, and ethyl methyl carbonate.

[0067] By selecting an organic solvent as the solvent, it becomes easier to isolate the oxidized cellulose obtained in the above process and the nanocellulose obtained by defibrating it. In addition, since the nanocellulose is obtained dispersed in the organic solvent, it becomes easier to mix it with the resin that dissolves in the organic solvent and the raw material monomer for the resin. EXAMPLES

[0068] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0069] <Method for evaluating viscosity stability> Aqueous slurries (50 g) containing Ishihara Sangyo Kaisha's titanium dioxide R-820 (5 mass%) and various nanocelluloses were prepared by varying the amount of nanocellulose added so that the initial viscosity of the slurry was 300 mPa·s when measured using the method described below. A Thinky mixer "Awatori Rentaro ARE-310" (mix mode, revolution: 2000 rpm, rotation: 800 rpm, 20 minutes) was used to mix the slurries. The viscosity was measured immediately after preparation (initial viscosity) and after standing for one week. The viscosity change rate was calculated using the following formula, and the viscosity stability was evaluated according to the following criteria. Viscosity change rate (%) = (viscosity of slurry after standing for 1 week) / (viscosity of slurry immediately after preparation) × 100 Viscosity stability criteria (absolute value of viscosity change rate) A: Less than 105% B: 105% or more, less than 110% C: 110% or more, less than 115% D: 115% or more The samples were left to stand indoors at 23±2°C.

[0070] <Viscosity measurement method> The initial viscosity of the slurry was measured by stirring with a spatula at a speed that did not introduce bubbles, and then measuring the viscosity at 25°C, 100 rpm (shear rate 200 s) using a Toki Sangyo Co., Ltd. E-type viscometer (TV-22). -1 The viscosity after standing for one week was also measured under the same conditions using the above equipment.

[0071] <Method for measuring nanocellulose fiber length and fiber width> The obtained nanocellulose dispersion was diluted 1,000 to 1,000,000 times with pure water, allowed to dry naturally on a mica substrate, and the shape of the nanocellulose was observed in AC mode using an Oxford Asylum scanning probe microscope "MFP-3D infinity." The fiber length was analyzed by binarizing the images obtained using the image processing software "ImageJ." For 100 or more fibers, the number-average fiber length was calculated as fiber length = "perimeter" ÷ 2. Regarding the fiber width, the software attached to the "MFP-3D infinity" was used to calculate the number average fiber width for 50 or more fibers, taking the cross-sectional height of the shape image as = fiber width.

[0072] <Example 1> As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. In a beaker, 350 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed, and pure water was added and stirred to adjust the effective chlorine concentration to 21% by mass. 35% by mass of hydrochloric acid was added thereto and stirred to make an aqueous solution with a pH of 11. The aqueous sodium hypochlorite solution was heated to 30° C. in a thermostatic water bath while being stirred at 100 rpm using a propeller-type stirring blade in a Shinto Scientific stirrer (Three-One Motor, BL600), and then 50 g of the cellulose-based raw material was added. After supplying the cellulosic raw material, the mixture was kept at 30°C in the same thermostatic water bath, and the pH during the reaction was adjusted to 11 by adding 48% by mass sodium hydroxide, and the mixture was stirred under the same conditions for 30 minutes using a stirrer. After completion of the reaction, the product was subjected to solid-liquid separation by suction filtration using a PTFE mesh filter with 20 μm openings, and the obtained oxidized cellulose was washed with pure water. Pure water was added to the oxidized cellulose to prepare a 5% dispersion, which was then processed 10 times at 200 MPa using a Sugino Machine ultra-high pressure homogenizer, Starburst Lab HJP-25005, to obtain a nanocellulose aqueous dispersion. In the ultra-high pressure homogenizer, the oxidized cellulose aqueous dispersion is circulated through the built-in ultra-high pressure defibrator to advance defibration. One pass through the defibrator is called one pass. The residual nitrogen components derived from N-oxyl compounds in nanocellulose were measured as nitrogen content using a total nitrogen trace analyzer (manufactured by Mitsubishi Chemical Analytech Co., Ltd., device name: TN-2100H), and the increase from the raw pulp was calculated, resulting in a value of less than 1 ppm.

[0073] <Example 2> The conditions were the same as in Example 1, except that the number of passes through the ultra-high pressure homogenizer was changed to 15 passes.

[0074] <Example 3> The conditions were the same as in Example 1, except that powdered cellulose (KC Flock W-100GK) manufactured by Nippon Paper Industries Co., Ltd. was used as the cellulosic raw material.

[0075] <Example 4> The conditions were the same as in Example 1, except that powdered cellulose (VP-1) from TDI Corporation was used as the cellulosic raw material.

[0076] <Example 5> The conditions were the same as in Example 1, except that the oxidized cellulose concentration in the oxidized cellulose dispersion during defibration was 2 mass %.

[0077] <Example 6> The conditions were the same as in Example 3, except that the oxidized cellulose concentration in the oxidized cellulose dispersion during defibration was 2 mass %.

[0078] <Example 7> The conditions were the same as in Example 3, except that the oxidized cellulose concentration in the oxidized cellulose dispersion during defibration was 2 mass % and the number of passes through the ultra-high pressure homogenizer was 8 passes.

[0079] <Example 8> The conditions were the same as in Example 3, except that the oxidized cellulose concentration in the oxidized cellulose dispersion during defibration was 3 mass %.

[0080] <Comparative Example 1> The conditions were the same as in Example 1, except that the stirring during the oxidation reaction was performed with a stirrer, and that pure water was added to the oxidized cellulose to prepare a 1% dispersion, which was then defibrated for 10 minutes using a Hielscher ultrasonic homogenizer "UP-400S" under conditions of CYCLE 0.5 and AMPLIYUDE 50. In the ultrasonic homogenizer, the ultrasonic oscillator was immersed in an aqueous dispersion of oxidized cellulose placed in a container, and defibration was promoted by the ultrasonic waves generated.

[0081] <Comparative Example 2> The conditions were the same as in Example 4, except that the oxidation reaction time was changed to 20 minutes.

[0082] <Comparative Example 3 (TEMPO oxidation)> 0.8 g of 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (TEMPO, Sigma-Aldrich) and 5 g of sodium bromide (Fujifilm Wako Pure Chemical Industries, Ltd.) were placed in a beaker, and 5000 mL of pure water was added. The mixture was then dissolved by stirring at 200 rpm using a propeller-type stirring blade of a Shinto Scientific stirrer (Three-One Motor, BL600). After heating to 25°C in a thermostatic water bath, 50g of softwood pulp (Sigma-Aldrich NIST RM 8495, bleached kraft pulp) mechanically defibrated into a cotton-like form was added as a cellulosic raw material, and 0.1M sodium hydroxide solution was added to make an aqueous solution of pH 10. Next, 131.5g of sodium hypochlorite aqueous solution (industrial grade) was added to start the reaction. After supplying the sodium hypochlorite aqueous solution, the pH during the reaction was adjusted to 10 by adding 0.1M sodium hydroxide while keeping the temperature at 25°C in the same thermostatic water bath, and stirring was performed under the same conditions with a stirrer for 120 minutes. After completion of the reaction, the product was subjected to solid-liquid separation by suction filtration using a PTFE mesh filter with 20 μm openings, and the obtained oxidized cellulose was washed with pure water. Pure water was added to the oxidized cellulose to prepare a 0.5% dispersion, which was then processed three times at 200 MPa using a Sugino Machine ultra-high pressure homogenizer called "Starburst Lab" to obtain a nanocellulose aqueous dispersion. The residual nitrogen component derived from N-oxyl compounds in the nanocellulose was measured as the nitrogen content under the same conditions as in Example 1, and the increase from the raw pulp was calculated to be 5 ppm.

[0083] The results of the nanocellulose obtained in Examples 1 to 8 and Comparative Examples 1 to 3 are summarized in Table 1 below. The cellulosic raw materials in Table 1 are as follows: Softwood: Softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) mechanically defibrated into a cotton-like form. · KC: Powdered cellulose manufactured by Nippon Paper Industries Co., Ltd. (KC Flock W-100GK) ·VP: TDI powdered cellulose (VP-1)

[0084] [Table 1]

[0085] [Table 2]

Claims

1. Nanocellulose having an average fiber length of 100 nm or more and 500 nm or less and an average fiber width of 2.0 nm or more and 4.5 nm or less, which satisfies the following condition A and contains carboxylated nanocellulose. Condition A: The standard deviation of fiber length is 600 nm or less.

2. 2. The nanocellulose of claim 1, wherein the standard deviation of the fiber length is 10 nm or more and 500 nm or less.

3. 3. The nanocellulose of claim 1 or 2, which is substantially free of N-oxyl compounds.

4. The nanocellulose according to any one of claims 1 to 3, which is produced by defibrating oxidized cellulose obtained by oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof.

5. A nanocellulose dispersion in which the nanocellulose according to any one of claims 1 to 4 is dispersed in a dispersion medium.

6. The method for producing nanocellulose according to any one of claims 1 to 4, comprising a step of defibrating oxidized cellulose obtained by oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof.

Citation Information

Patent Citations

  • Surfaceemodifying composition and synthetic resin film coated therewith

    JP1981055432A

  • Method for producing nanofibrillated cellulose

    JP2016501926A

  • Binding agent, electrode slurry, electrode and method of manufacturing the same, and secondary battery

    JP2017130451A

  • Dispersion liquid of cellulose nanofibers and method for producing the same

    JP2017193814A

  • H type carboxylated cellulose nanofibers

    JP2018162549A